GENDER DIFFERENCES IN WRITING COMPLEX SENTENCES - Ridawati Sirait; Noflin Wenas; Eri Kurniawan (LPPM Politeknik Saint Paul Sorong, 2023)
This study mainly to describe the gender differences in wtiting complex sentences. Twelve (12) students grade eight (8) junior high school students in two different places, one is in North Sumatera and another one is in Manado – 6 males and 6 females – were instructed to write an informal letter to their friends. The writers use a descriptive qualitative method to classify and analyze the writing complex sentences. The object of this study was 12 students’ informal letter. The findings of this research are following: 1T-units (1 independent clause) for male is 36% and 1T-units for female is 64%; it shows a big gap. However, the 2T-units (2 independent clauses) for male is 21% and for female is 17%, and 3T-units (3 independent clauses) for male is 11% and for female is also 11%.